ARFI elastography as a complementary diagnostic method for mammary neoplasia in female dogs – preliminary results. (7th August 2014) - Feliciano, M. A. R.; Maronezi, M. C.; Pavan, L.; Castanheira, T. L.; Simões, A. P. R.; Carvalho, C. F.; Canola, J. C.; Vicente, W. R. R.
<x xml:space="preserve">Abstract</x> OBJECTIVES To evaluate the applicability of acoustic radiation force impulse elastography as a complementary method in diagnosing mammary neoplasia in dogs. METHODS Mammary tumours from 50 female dogs were evaluated and divided into two groups: G1 (benign tissue) and G2 (malignant tumours). The nodules were assessed by B‐Mode ultrasonography, qualitative and quantitative acoustic radiation force impulse elastography and histopathology. RESULTS B‐Mode ultrasound examination was ineffective at separating the tumours into the two groups. Likewise, there was no correlation between the grayscale images of the mammary tissue by qualitative elastography. A difference was found in the deformity of the mammary masses between the malignant and benign groups (P = 0 · 002). Using quantitative elastography, the mean values of shear velocity were 3 · 33 m/s for malignant tumours and 1 · 28 m/s for benign tissue (P < 0 · 0001). CLINICAL SIGNIFICANCE The use of acoustic radiation force impulse elastography may help to differentiate between malignant and benign mammary neoplasms.